Impact of Transformational Leadership, Work Motivation, and Organizational Culture on Soldier Performance: Study on 9/SDK Cavalry Battalion - Miftakhurohman Miftakhurohman; Veronika Santi Paramita (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2024)
The Cavalry Unit constitutes a component of the Combat Assistance Unit, which is under the ownership of the Indonesian Army. In terms of both security and battle, the primary objective of the Cavalry Battalion is to ensure that troopers exhibit peak performance. Nevertheless, the leadership frequently fails to address the issue of poor performance among troops. The objective of this study is to ascertain the impact of transformational leadership, work motivation, and organizational culture on the performance of soldiers. The study methodology employed a descriptive approach using quantitative methods. The study sample consisted of nine soldiers randomly recruited from the 87 Cavalry Battalion. The study findings indicate that transformational leadership, work motivation, and corporate culture have a positive impact on troop performance, both individually and collectively. Efforts to enhance overall performance in the 9th Cavalry Battalion/Satya Dharma Kala necessitate the integration and optimization of three key factors: transformational leadership, work motivation, and organizational culture.